Addition of clidinium-C to the 14-day proton-pump inhibitor-based triple therapy for Helicobacter pylori eradication - Mohammadreza Seyyedmajidi; Saba Homapoor; Elahe Zanganeh; Mohammad Dadjou; Shahab Eskandari-Nejad; Mohammad-Hadi; Jamshid Vafaeimanesh (Babol University of Medical Sciences, 2016)
Background: Triple therapy with a proton pump inhibitor and two antibiotics in Helicobacter pylori (HP) eradication is widely accepted, but this combination fails in a considerable number of cases. The aim of this study was to assess the effect of clidinium-C addition on HP eradication and to investigate the efficacy and safety of clidinium-C in prevention of drugs' side effects. Methods: A total of 200 histopathologically confirmed HP positive peptic ulcer enrolled in this study which were randomly assigned to two treatment groups: OAC (20 mg omeprazole bid, 1000 mg amoxicillin bid and 500 mg clarithromycin bid) and OAC + clidinium-C. The effect of treatment and adverse effects were compared 6 weeks after completion of treatment. A13C-urea breath test was performed to confirm HP eradication. Results: A total of 184 patients (90 in group A and 94 in group B) completed the treatment protocols. HP eradication was achieved in 71.1% in OAC versus 72.3% in OCA+clidinium-C, (P=0.73). The frequencies of abdominal pain and stool abnormality, among the side effects recorded during the therapy period, were significantly lower in group B (OCA+clidinium-C) (P=0.01 and P=0.001, respectively). Conclusion: Addition of clidinium-C to OCA triple therapy decreases abdominal pain and frequency of stool abnormalities without affecting HP eradication rate. Based on these findings addition of clidinium-C may increase patient's compliance.